Evaluating the Potential Association Between Lipoprotein(a) and Atherosclerosis (from the Mediators of Atherosclerosis Among South Asians Living in America Cohort) - Huffman, Mark D.; Kandula, Namratha R.; Baldridge, Abigail S.; Tsai, Michael Y.; Prabhakaran, Dorairaj; Kanaya, Alka M. (The American journal of cardiology, 2019)
We sought to report the distribution of Lp(a) levels in the Mediators of Atherosclerosis among South Asians Living in America cohort of participants who were free from clinical atherosclerotic cardiovascular disease (ASCVD) at baseline and to evaluate the cross-sectional association with atherosclerosis measured by coronary artery calcification (CAC) and carotid intima media thickness. Among 886 participants (mean [SD] age: 55.4 [9.4] years, 54% male), median lipoprotein (a) level was 17 (9, 33) mg/dl. Compared with the lowest quartile (9 mg/dl), subjects in the highest Lp(a) quartile (33 to 178 mg/dl) were more likely to be women (51% vs 37%, p <0.01) and had a higher mean (SD) total cholesterol (193 [37] mg/dl vs 181 [35] mg/dl, p <0.01). CAC was present in 42% and both the presence and degree of CAC was similar across Lp(a) quartiles (p = 0.58). Median Interquartile range (IQR) common and internal carotid intima-media thickness (IMT) thicknesses were 0.84 (0.73, 0.98) mm and 1.12 (0.95, 1.34) mm, respectively, and were also similar across Lp(a) quartiles. After adjustment for cardiovascular risk factors, Lp(a) quartile had no association with prevalent CAC (p = 0.98), internal carotid IMT (p = 0.46), or common carotid IMT (p = 0.97). Among South Asian Americans, mean Lp(a) levels were higher than previous reports among Whites, Hispanic/Latino, and Chinese-Americans but lower than in Blacks. Unlike findings from other race/ethnic groups, Lp(a) levels were not associated with atherosclerosis among South Asian Americans.